CARDIOVASCULAR RISK PROFILE OF A YOUNG ADULT POPULATION WITH HIGH RISK FOR OBSTRUCTIVE SLEEP APNEA SCREENED BY STOP-BANG AND EPWORTH SLEEPINESS SCALE IN A PRIMARY HEALTH CARE UNIT. (April 2021) - Barbalho, Daniella Gomes; De Souza Mello, Tomas; Zink, Luciana Oliveira; Louzada, Vinicius Leiria Teixeira; Borges, Rodrigo Eugênio Vinuto; Ribeiro, Sávio Ferreira; De Hollanda, João Victor Gonçalves; Botelho, Bruna Gopp; Da Silva, Amanda Oliveira; Silva, Rodrigo; Ushijima, Natalia Rossilho Moyses; Kendler, Daniel Barreto; et al.
Abstract: Objective: To establish the relationship between cardiovascular (CV) risk profile and detected risk of Obstructive Sleep Apnea (OSA) in two questionnaires - STOP-BANG (SB) and Epworth Sleepiness Scale (ESS), in a young population of adults registered in a Primary Health Care unit in Rio de Janeiro, Brazil. Design and method: This cross-sectional population study enrolled adults between 20–50 years old, registered in a primary healthcare unit in Rio de Janeiro. A database is being developed including sociodemographic and anthropometric data, and CV risk factors. Office blood pressure (BP) and Home Blood Pressure Monitoring (HBPM) (7-day protocol) (Omron-705CP). Moreover, OSA was investigated by SB and ESS. Patients with a high risk for OSA in either of these two questionnaires were subsequently assigned for polysomnography (PSG). Results: A total of 562 subjects were evaluated [40% males, 38.9 ± 8.8 years], where 151 (26.9%) were identified as high risk for OSA by the SB questionnaire and 210 (37.4%) by ESS. The most common CV risk factor was physical inactivity (43%), followed by dyslipidemia (38%) and obesity (28%). By OBP, the prevalence of hypertension was 13.4% while by HBPM was 18.6%, with a low concordance between them (kappa = 0.472). Subjects with a high risk at SB are older, with a higher prevalence of obesity, hypertension and higher office BP and HBPM. On the other hand, individuals with high-risk by ESS were more obese, with increased waist circumference, higher prevalence of dyslipidemia and metabolic syndrome. Nevertheless, there was no difference in BP levels. Among the subjects submitted to PSG, 46% had a diagnosis of OSA (AHI higher 5/hour) and 23% of moderate/severe OSA (AHI higher 15/hour). The best predictor of AOS was SB, positive in 100% of subjects with moderate/severe OSA, while ESS was positive in only 20% of them. Conclusions: This young and apparently healthy population presented a high prevalence and risk for OSA. The SB had a higher association with higher BP levels, while ESE was associated with a worse metabolic profile. SB questionnaire seems to be the best predictor for moderate/severe OSA in this young adult population.